Cystic and necrotic papillary renal cell carcinoma: prognosis, morphology, immunohistochemical, and molecular-genetic profile of 10 cases - Peckova, Kvetoslava; Martinek, Petr; Pivovarcikova, Kristyna; Vanecek, Tomas; Alaghehbandan, Reza; Prochazkova, Kristyna; Montiel, Delia Perez; Hora, Milan; Skenderi, Faruk; Ulamec, Monika; Rotterova, Pavla; Daum, Ondrej; et al. (Annals of diagnostic pathology, 2017)
Conflicting data have been published on the prognostic significance of tumor necrosis in papillary renal cell carcinoma (PRCC). Although the presence of necrosis is generally considered an adverse prognostic feature in PRCC, we report a cohort of 10 morphologically distinct cystic and extensively necrotic PRCC with favorable biological behavior. Ten cases of type 1 PRCC with a uniform morphologic pattern were selected from the 19 500 renal tumors, of which 1311 were PRCCs in our registry. We focused on precise morphologic diagnosis supported by immunohistochemical and molecular-genetic analysis. Patients included 8 men and 2 women with an age range of 32-85 years (mean, 62.6 years). Tumor size ranged from 6 to 14 cm (mean, 9.4 cm). Follow-up data were available in 7 patients, ranging from 0.5 to 14 years (mean, 4 years). All tumors were spherical, cystic, and circumscribed by a thick fibrous capsule, filled with hemorrhagic/necrotic contents. Limited viable neoplastic tissue was present only as a thin rim in the inner surface of the cyst wall, consistent with type 1 PRCC. All cases were positive for AMACR, OSCAR, CAM 5.2, HIF-2, and vimentin. Chromosome 7 and 17 polysomy was found in 5 of 9 analyzable cases, 2 cases demonstrated chromosome 7 and 17 disomy, and 1 case showed only chromosome 17 polysomy. Loss of chromosome Y was found in 5 cases, including 1 case with disomic chromosomes 7 and 17. No VHL gene abnormalities were found. Papillary renal cell carcinoma type 1 can present as a large hemorrhagic/necrotic unicystic lesion with a thick fibroleiomyomatous capsule. Most cases showed a chromosomal numerical aberration pattern characteristic of PRCC. All tumors followed a nonaggressive clinical course. Large liquefactive necrosis should not necessarily be considered an adverse prognostic feature, particularly in a subset of type 1 PRCC with unilocular cysts filled with necrotic/hemorrhagic material.
Keywords: nádory ledvin; Male; hybridizace in situ fluorescenční; karcinom z renálních buněk; prognóza; chromozomální aberace; Adult; Kidney Neoplasms; Aged; dospělí; imunohistochemie; mužské pohlaví; senioři; molekulární patologie; Chromosome Aberrations; senioři nad 80 let; papilární karcinom; lidé; ženské pohlaví; Immunohistochemistry; Biomarkers, Tumor; Humans; Carcinoma, Papillary; Aged, 80 and over; Pathology, Molecular; Carcinoma, Renal Cell; In Situ Hybridization, Fluorescence; Prognosis; Female; lidé středního věku; nádorové biomarkery; Middle Aged